Annotation: Hyperlexia: disability or superability? - Grigorenko, Elena L.; Klin, Ami; Volkmar, Fred (Journal of child psychology and psychiatry, 2003)
Background: Hyperlexia is the phenomenon of spontaneous and precocious mastery of single‐word reading that has been of interest to clinicians and researchers since the beginning of the last century. Methods: An extensive search of publications on the subject of hyperlexia was undertaken and all available publications were reviewed. Results: The literature can be subdivided into discussions of the following issues: (1) whether hyperlexia is a phenomenon that is characteristic only of specific clinical populations (e.g., children with developmental delays) or whether it can also be observed in the general population; (2) whether hyperlexia is a distinct syndrome comorbid with a number of different disorders or whether it is a part of the spectrum of some other clinical condition(s); (3) whether hyperlexia should be defined through single‐word reading superiority with regard to reading comprehension, vocabulary, general intelligence, any combination of the three, or all three characteristics; (4) whether there is a specific neuropsychological profile associated with hyperlexia; (5) whether hyperlexia is characterized by a particular developmental profile; and (6) whether hyperlexia should be viewed as a disability (deficit) or superability (talent). Conclusions: We interpret the literature as supporting the view that hyperlexia is a superability demonstrated by a very specific group of individuals with developmental disorders (defined through unexpected single‐word reading in the context of otherwise suppressed intellectual functioning) rather than as a disability exhibited by a portion of the general population (defined through a discrepancy between levels of single‐word reading and comprehension). We simultaneously argue, however, that multifaceted and multi‐methodological approaches to studying the phenomenon of hyperlexia, defined within the research framework of understanding single‐word reading, are warranted and encouraged.